DEVELOPMENT OF EDUCATIONAL OPTICAL MARK RECOGNITION SYSTEM WITH NI LABVIEW - (:unkn) unknown (INT ORGANIZATION CENTER ACAD RESEARCH, 2017)
This study aims to develop a software, which can read the test type examination paper with less effort under low cost. The software is based on optical mark recognition system in order to read multiple choice test exams answer sheets based on image processing. The reading and evaluation of exam papers is an important activity that takes a significant portion of the trainers' time. Accurate implementation of this process is extremely important in terms of evaluation of education. In the application part of this work, a software realized by using the NI LabVIEW software was used to automatically read answer papers scanned in JPEG format in any copier without the need for an optical reading device. The preliminary tests of the developed software were made with 50 answer papers prepared and it was seen that successful results were obtained. The system, which requires only a computer and JPEG format scanning, is evaluated to have the potential to be used by a much wider set of teachers besides simplicity and high speed and accuracy compared to expensive optical reading devices.
Keywords: reading of test type exam; image processing; optical mark recognition; automated data processing